MANAJEMEN KESISWAAN DALAM MENGTASI KENAKALAN SISWA DI SEKOLAH MENENGAH PERTAMA - Nahla Annida; Triono Ali Mustofa (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
Student management is an arrangement or arrangement of all forms of activity related to students. From entering the school to leaving the student. Student management is one of the keys to the success of an educational institution. This study aims to describe student management and find out how student management is in SMP Muhammadiyah 5 Surakarta. The method used is descriptive qualitative. In seeking information, researchers used the interview method and also a literature study. The results of the research that has been carried out show that student management at SMP Muhamadiyah 5 Surakarta has been running well. All activities and rules have been created and obeyed by the entire school community.Student management aims to organize various activities in the field of student affairs so that learning activities are carried out and school runs smoothly, orderly, and orderly. Some experts argue that the management objectives of participants' Education are to create conditions good school environment and so that students can study in an orderly manner so that it can achieve effective and efficient teaching goals. There is three main tasks in the field of management for students to achieve these goals namely student acceptance, activities learning progress as well as guidance and discipline development.